A possible neurophysiological correlate of audiovisual binding and unbinding in speech perception - Ganesh, Attigodu C.; Berthommier, Frédéric; Vilain, Coriandre; Sato, Marc; Schwartz, Jean-Luc (Frontiers in Psychology, 2014)
Audiovisual speech integration of auditory and visual streams generally ends up in a fusion into a single percept. One classical example is the McGurk effect in which incongruent auditory and visual speech signals may lead to a fused percept different from either visual or auditory inputs. In a previous set of experiments, we showed that if a McGurk stimulus is preceded by an incongruent audiovisual context (composed of incongruent auditory and visual speech materials) the amount of McGurk fusion is largely decreased. We interpreted this result in the framework of a two-stage "binding and fusion" model of audiovisual speech perception, with an early audiovisual binding stage controlling the fusion/decision process and likely to produce “unbinding” with less fusion if the context is incoherent. In order to provide further electrophysiological evidence for this binding/unbinding stage, early auditory evoked N1/P2 responses were here compared during auditory, congruent and incongruent audiovisual speech perception, according to either prior coherent or incoherent audiovisual contexts. Following the coherent context, in line with previous EEG/MEG studies, visual information in the congruent audiovisual condition was found to modify auditory evoked potentials, with a latency decrease of P2 responses compared to the auditory condition. Importantly, both P2 amplitude and latency in the congruent audiovisual condition increased from the coherent to the incoherent context. Although potential contamination by visual responses from the visual cortex cannot be discarded, our results might provide a possible neurophysiological correlate of early binding/unbinding process applied on audiovisual interactions.